FUNCTION AND SIGNIFICANCE OF TEACHING TRANSLATION IN ELT - Dumbadze, Lela (Online Journal of Humanities ETAGTSU, 2023)
This article explores the role and significance of teaching translation and particularly teaching creative translation in the process of Teaching English as a Second Language. The issue of creative (real) translation, which is usually preceded by a pedagogical translation defined as information about the language learner’s level of language proficiency (Vermes, 2010), has been underestimated as part of teaching English as a second language in the higher education system. The information regarding this issue in Georgian academic publications on the topic is scarce whereas more supporters of this idea among specialists from overseas (Higgins & Ryland, 2019; Machida, 2011, amongst others) have appeared. The empirical data this article is based on were collected from the electronic questionnaire filled out by the teachers delivering practical courses in English at the Department of English Philology at Ivane Javakhishvili Tbilisi State University. The questionnaire included questions about the importance, advantages or disadvantages of teaching translation to students. The analysis of the data revealed specific advantages of creative translation regarding enhancing students’ command of the language, boosting self-confidence and preparing them for the challenges they may have to deal with in their future careers. On the other hand, among the disadvantages, several factors were mentioned including assessment issues, the status of the course and difficulties of its incorporation into the curriculum of the program. Full Text (PDF)